2021
DOI: 10.4274/haseki.galenos.2021.7383
|View full text |Cite
|
Sign up to set email alerts
|

Antibody False Positivity Among COVID-19 Convalescent Plasma Donors: A Comparative Study from the Turkish Red Crescent Blood Center

Abstract: During our routine work at the Turkish Red Crescent (TRC) laboratories, human immunodeficiency virus (HIV) 1/2 antibody false-positive results were observed among Coronavirus disease-2019 convalescent plasma (CP) donors more frequently than healthy donors. We aimed to determine anti-HIV 1/2 antibody false-positivity rates among the CP donors and healthy blood donors. Methods:The present study was designed as a cross-sectional study which was a type of observational study. Total 3689 donations from 2593 donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…This study adds support to previous publications reporting an increase in HIV false-positive results during and after COVID-19 pandemic [10–14] and gives support to consider SARS CoV-2 infection among possible causes of false-positive ELISA results, as they exhibited the same rate observed in other conditions not linked to the HIV infection [5]. The reporting of this finding is crucial to inform health authorities and should be dispersed along with virology testing providers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study adds support to previous publications reporting an increase in HIV false-positive results during and after COVID-19 pandemic [10–14] and gives support to consider SARS CoV-2 infection among possible causes of false-positive ELISA results, as they exhibited the same rate observed in other conditions not linked to the HIV infection [5]. The reporting of this finding is crucial to inform health authorities and should be dispersed along with virology testing providers.…”
Section: Discussionsupporting
confidence: 82%
“…HIV and SARS-CoV surface glycoproteins present a certain degree of homology and shared epitope motifs [9]. Indeed, there have been several reports in 2020 and 2021 of false-positive results in HIV screening assays in individuals with acute or past SARS CoV-2 infection [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The work of other researchers linked an acute SARS-CoV-2 infection to HIV test reactivity and suggested but did not demonstrate the presence of cross-reactive Abs [ 15 , 17 , 18 , 19 , 20 ]. SARS-CoV-2 spike-specific IgM peaks 2–5 weeks after the onset of symptoms [ 31 , 32 ] but decays quickly.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the previously recognized interfering reagents, three cohort studies found that coronavirus disease (COVID-19) was significantly associated with false-positive results in the fourth-generation HIV screening tests Elecsys HIV Duo (Roche) [ 14 , 15 ] and Genscreen Ultra HIV Ag-Ab (Bio-Rad) [ 16 ]. Further, severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2)-associated HIV test reactivity was linked in case studies to additional HIV screening tests including Elecsys HIV Combi PT (Roche) [ 17 ], VIDAS HIV Duo Ultra (BioMérieux) [ 18 ], Vitros HIV combo (Ortho Clinical Diagnostics) [ 19 ], Architect HIV Ag/Ab Combo (Abbott) [ 18 , 20 , 21 ], or unspecified tests [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation